The protagonist's image in Palestinian novels after Oslo accords in light of critical discourse analysis: A reading of "when the wolves grow old and velvet" - Harb, Khalil Mahmoud; Khoury, Musa Mitri (Journal of Arabic Language Sciences and Literature, 2025)
The research aims to explore the representations of the hero in Palestinian literature after the Oslo Agreement. The novels "When the Wolves Grow Old" and "Velvet" serve as the sample for this research, and its main issue highlights the fragmentation and changes in the image of the hero within these two novels. The research draws on theoretical frameworks from the Critical Discourse Analysis group, particularly Fairclough, who focused on studying the role of language in maintaining and altering power relations in society, as well as the methods of language analysis that serve this purpose, enhancing people's awareness of it, and their ability to resist and change it. The research includes an introduction and two main sections. The introduction addresses the development of Palestinian literature through the influence of historical and cultural events. It presents the two sample novels: "When the Wolves Grow Old" by Jamal Naji (2005) and "Velvet" by Hazem Habayeb (2016), selected from varying time frames after 1993. The first section is dedicated to a theoretical framework that includes a preamble about the image of the hero in Palestinian literature before Oslo, along with the concepts of the Critical Discourse Analysis group. The second section focuses on the representations of the hero in the two sample novels, examining the image of the hero in each novel separately, followed by a comparison of the collective images of the hero in both novels, revealing the underlying ideology and the series of changes that have occurred in Palestinian literature in general after Oslo, and specifically regarding the image of the hero. The research concludes that the "Oslo Authority" has impacted the discourse of Palestinian literature by dismantling the repetitive and consumed image of the hero found in earlier novels, replacing it with an ordinary person living under political and social conditions that had been absent from the Palestinian narrative scene for years.
Keywords: Critical Discourse Analysis; hero; Palestinian novel; Velvet; When the Wolves Grow Old; Oslo